Female Ownership of Fixed Assets in Nepal: A Regional Perspective - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2018)
Fixed assets especially house and land have significant importance in wealth, social security and power in Nepal. Ownership over these assets has greater implications in women’s status within households and communities. This also decides the economic dependence or independence and provides the means to be engaged in productive economic activity. The present study aims at analyzing the regional pattern of female ownership of fixed assets- house and land. Relevant data were acquired from a desk review of published and unpublished literature including online database. The study finds that there is a great gender discrepancy in ownership of fixed assets in Nepal and this varies across ecological zones and provinces. Female ownership of both land and house is associated with 10.7 percent while only 9.0 percent have ownership of land only. Tarai shows relatively positive condition as compared to other ecological zones with female ownership of 12.3 percent households with house and land and 10.5 percent with only land. Among provinces, the most negative situation exists in the province six as compared to others. The socio-cultural barriers are still a major challenge for women’s ownership of property in Nepal. The Third Pole: Journal of Geography Vol. 17: 73-82, 2017